2014
DOI: 10.5146/tjpath.2014.01285
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological study to evaluate oral lichen planus for the establishment of clinical and histopathological diagnostic criteria

Abstract: Objective: Lichen planus and lichenoid lesions affecting the oral cavity show similar clinico-pathological features creating a diagnostic dilemma. Hence, the aim of the present study was to establish a clinical and histopathological correlation in the diagnosis of oral lichen planus, based on the modified wHO diagnostic criteria of oral lichen planus and oral lichenoid lesions proposed by Van der Meij and Van der waal in 2003. Material and Method:In the present study, 100 cases of oral lichen planus were clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
11
0
3
Order By: Relevance
“…Our results confirm that there is no relation between the different clinical and histopathological subtypes of this disease, as has been presented in other studies (2,7,10,11). Therefore, we consider that the histopathological characteristics observed in the biopsies of this disorder should not be used as infallible and specific diagnostic criteria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm that there is no relation between the different clinical and histopathological subtypes of this disease, as has been presented in other studies (2,7,10,11). Therefore, we consider that the histopathological characteristics observed in the biopsies of this disorder should not be used as infallible and specific diagnostic criteria.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies (2,7,10,11) agree, that the application of the WHO diagnostic criteria, modified by van der Meij and van der Waal in 2003 (8) for lichenoid processes, has proven to be inefficient in establishing a good correlation between the clinical and histopathological diagnosis, and to differentiate between oral lichen planus (OLP) and oral lichenoid lesions (OLL). Nonetheless, the study by Rad et al in 2009 (12), showed a good correlation between the clinical and the histopathological aspects.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization, OLP is a highly prevalent disease that can progress to oral cancer. It is also considered a potentially malignant disorder that should be closely supervised …”
Section: Introductionmentioning
confidence: 99%
“…However, a lack of validated clinical or histological criteria and substantial interobserver variability has been documented for both clinical and histological assessment . A recent study showed only mild to moderate clinicopathological correlation in the diagnosis of OLP . The absence of histopathological correlation may reflect variation in the nature (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] A recent study showed only mild to moderate clinicopathological correlation in the diagnosis of OLP. 9 The absence of histopathological correlation may reflect variation in the nature (i.e. erosive vs. hyperkeratotic), chronicity and location of OLP lesions.…”
Section: Introductionmentioning
confidence: 99%